Photovoltaic limitations of BODIPY:fullerene based bulk heterojunction solar cells - Baran, Derya; Tuladhar, Sachetan M.; Economopoulos, Solon P.; Neophytou, Marios; Savva, Achilleas; Itskos, Grigorios; Othonos, Andreas; Bradley, Donal D.C.; Brabec, Christoph J.; Nelson, Jenny; Choulis, Stelios A. (My University, 2017)
The photovoltaic performance of blends of a series of 4,4′-Difluoro-4-bora-3a,4a-diaza-s-indacenes)-based (BODIPY) conjugated polymers donors with fullerene electron acceptors is investigated. Despite the high Voc values observed, solar cell device yields relatively low power conversion efficiencies. Our study takes into account the materials’ structure-property relationship, light harvesting capabilities, charge transport, collection properties and morphological characteristics to elucidate factors affecting the photovoltaic performance in this class of polymers. We show that elimination of low molecular weight species and suitable electrodes for hole collection can be used to overcome some of the observed limitations on photovoltaic performance.
Keywords: BODIPY polymer donors; Organic solar cells; Charge transport; Collection; Fractionation process; Morphology